La falta de legítimo contradictor como excepción previa no subsanable requiere normativa expresa en el COGEP - Alvarado Pinela, Tania Fernanda (2018)
The General Organic Code of Process entered into force on May 25, 2016, replacing the Code of Civil Procedure, this new legal body allowed that in our Ecuadorian legislation several transcendental changes in the procedural scope were developed, one of them is the presentation of the previous exceptions that can be rectified and not remedied, those that in the previous code were determined as dilatory and peremptory. Based on time, on the subject, object of our study, whose name is, the lack of a legitimate contradictor as a previous exception that can’t be remedied requires express regulations in the COGEP, which, being part of the exception of lack of legitimacy in the case, does not distinguish between the incomplete conformation of litisconsorcio, with the lack of legitimate contradictor, that allows the judge to solve in a grounded manner based on the nature of each of them……